Electrochemical Mechanism of Trivalent Chromium Reduction in ChCl-EG Deep Eutectic Solvents Containing Trivalent Chromium. Issue 10 (22nd June 2020) - Qian, Huixuan; Sun, Jie; Li, Qisong; Sun, Haijing; Fu, Xu
Abstract : In this work, the cyclic voltammetry (CV) was used to investigate the redox process of Cr(III) on glassy carbon electrode (GC) in deep eutectic solvents (DESs), prepared using choline chloride (ChCl) and ethylene glycol (EG). The anode and cathode branches of the CV curve meant the process of deposition/dissolution equilibrium of trivalent chromium. The equilibrium potential ( E eq ) of Cr(III)/Cr(0) was −0.964 V (vs Ag QRE). The analysis of the potentiostatic current density transient (chronoamperometry (CA)) results showed that the electrodeposition process of Cr(III) involved multiple processes, mainly j ad, j 3D and j WR . By calculating the amount of charge ( Q ad %, Q 3D %, and Q WR %) in each process, it can be found that the contribution rate could be controlled by the potential to increase Q 3D %. The kinetic parameters of Cr nucleation/growth rate were determined from the standard model of 3D nucleation of diffusion-control, such as nucleation rate (A), active centre number density (N 0 ), and diffusion coefficient (D) . The ln( A ) and η were used to calculate the nucleated Gibbs free energy (Δ∼ G(n c )), the critical core size (n c ), the current exchange density (j 0 ), the transfer coefficient (α), and the surface tension (σ) . The chromium coating was constituted by particles of Cr(0), Cr2 O3 and Cr(OH)3 .